Understanding fibroblast heterogeneity in the skin. Issue 2 (February 2015) - Driskell, Ryan R.; Watt, Fiona M.
Highlights Fibroblasts are functionally heterogeneous. Heterogeneity is attributable to distinct lineages. Fibroblasts are regulated by epidermal Wnt signalling.